Optimization of biodiesel production by microwave irradiation-assisted transesterification for waste cooking oil-Calophyllum inophyllum oil via response surface methodology. (15th February 2018) - Milano, Jassinnee; Ong, Hwai Chyuan; Masjuki, H.H.; Silitonga, A.S.; Chen, Wei-Hsin; Kusumo, F.; Dharma, S.; Sebayang, A.H.
Graphical abstract: Highlights: Microwave irradiation provides unique thermal effects for chemical synthesis. W70CI30 biodiesel of 97.65% is obtained in 9.15 min of transesterification process. Optimised mixture comprises of 96.72% of FAME yield with total glycerol of 0.125%. Biodiesel produced fulfil the specifications given by the ASTM and EN standards. Microwave irradiation biodiesel synthesis is beneficial for the industrial scale. Abstract: In this study, microwave irradiation-assisted alkaline-catalysed transesterification was used to produce W70CI30 biodiesel from a mixture of waste cooking oil and Calophyllum inophyllum oil. The methanol/oil ratio, catalyst concentration, stirring speed, and reaction time were optimized using response surface methodology based on the Box-Behnken experimental design in order to maximize the biodiesel yield. The quadratic response surface regression model was used to predict the biodiesel yield. It is found that the optimum methanol/oil ratio, catalyst concentration, stirring speed, and reaction time are 59.60 (v/v)%, 0.774 (w/w)%, 600 rpm, and 7.15 min, respectively, and the predicted biodiesel yield is 97.40%. Experiments were conducted using the optimum process parameters and the average biodiesel yield is 97.65%, which is in excellent agreement with the predicted value. The physicochemical properties of the W70CI30 biodiesel produced using the optimum process parameters were measured and it is found that the biodiesel has significantly higher oxidation stability (18.03 h) compared with the waste cooking oil biodiesel (4.61 h). In addition, the physicochemical properties and cold flow properties of the biodiesel fulfil the fuel specifications stipulated in the ASTMD6751 and EN 14214 standards. It can be concluded that microwave irradiation-assisted transesterification is effective to boost the biodiesel yield and produce biodiesel of superior quality. In addition, this method significantly reduces the reaction time of the transesterification process to 9.15 min and the process is energy-efficient. It is believed that the findings of this study will be beneficial for microwave irradiation-assisted biodiesel synthesis on the industrial scale.